Kerja Anatomi Tubuh dalam Yoga Asana - Adnyani, Ni Made (Institut Hindu Dharma Negeri Denpasar, 2018)
Anatomy is a field of knowledge that studies the structure of the human body. A good understanding of anatomy and its relationship to asanas is essential so that yoga practitioners can keep their body safe, comfortable and the mind remains stable. Yoga has an integrated working principle in the human body. An important element that distinguishes yoga practice with other exercises is the linkage of breath, posture and movement. By the yogis, they are based on the concept of prana and apana; sthira and sukha; brahmana and laghana; and sukha and dukha. The flow of breath is associated with prana and apana, postural stability associated with sthira and sukha, and sukhaduhka and movements associated with brahmana and laghana.